A cultural history of objects - Hicks, Dan, 1972-; Whyte, William (William Hadden) (London : Bloomsbury Academic, 2021)
"How have objects have been created, used, interpreted and set loose in the world over the last 2500 years? Over this time, the West has developed particular attitudes to the material world, at the centre of which is the idea of the object. This set brings together over 50 scholars, in 1776 pages, to examine how the world of human subjects shapes and is shaped by the world of material objects. Chapter titles are identical across each of the volumes. This gives the choice of reading about a specific period in one of the volumes, or following a theme across history by reading the relevant chapter in each of the six.The themes (and chapter titles) are: Objecthood; Technology; Economic Objects; Everyday Objects; Art; Architecture; Bodily Objects; Object Worlds.The six volumes cover: 1 – Antiquity (500 BCE to 500 CE); 2 – Medieval Age (500 to 1400); 3 – Renaissance (1400 to 1600); 4 – Age of Enlightenment (1600 to 1760); 5 – Age of Industry (1760 to 1900); 6 – Modern Age (1900 to the present)."--
Volume 1: A cultural history of objects in antiquity / edited by Robin Osborne -- volume 2: A cultural history of objects in the medieval age / edited by Julie Lund and Sarah Semple -- volume 3: A cultural history of objects in the renaissance / edited by James Symonds -- volume 4: A cultural history of objects in the age of enlightenment / edited by Audrey Horning -- volume 5: A cultural history of objects in the age of industry / edited by Carolyn White -- volume 6: A cultural history of objects in the modern age / edited by Laurie Wilkie and John Chenoweth.
Sisältää bibliografisia viitteitä ja hakemiston.
Keywords: Material culture; aineellinen kulttuuri; esineet; kulttuurihistoria; materiell kultur; föremål; kulturhistoria